2015
DOI: 10.1016/j.amjmed.2015.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin and Prealbumin in Calorically Restricted, Nondiseased Individuals: A Systematic Review

Abstract: In these otherwise healthy subjects, serum albumin and prealbumin levels are not "markers of nutritional status." The "markers" failed to identify subjects with severe protein-calorie malnutrition until extreme starvation. That is, they failed to identify healthy individuals who would benefit from nutrition support, becoming abnormal only when starvation was already obvious. In contrast, serum albumin and prealbumin levels are known to fall promptly with injury or illness regardless of nutrient intake. They ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 65 publications
7
124
1
1
Order By: Relevance
“…This review consisted mainly of studies performed in adult patients with anorexia nervosa, whereas the studies in children and young adolescents were limited by small sample sizes, as the population numbers ranged from one to 25 (8).…”
Section: Discussionmentioning
confidence: 99%
“…This review consisted mainly of studies performed in adult patients with anorexia nervosa, whereas the studies in children and young adolescents were limited by small sample sizes, as the population numbers ranged from one to 25 (8).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 63 studies, which included 2125 patients and investigated the effects of starvation on serum albumin levels in otherwise healthy individuals, reported that the levels remained normal until the patients reached extreme states of starvation (BMI < 12 or length > 6 weeks of starvation) when the malnutrition was already physically evident. Hence, it was concluded that albumin cannot be reliably used as a marker for diagnosing protein-calorie malnutrition [19]. Similarly, a case-control study that compared 14 anorexia nervosa patients with 15 healthy subjects reported that serum albumin levels did not vary in individuals with anorexia nervosa compared with controls during a follow-up of one year [20].…”
Section: Laboratory/serum Markersmentioning
confidence: 99%
“…Since children with motility disorders often have GI fluid losses, checking electrolytes, blood urea nitrogen (BUN), and creatinine is essential. In general, serum albumin and serum prealbumin, long considered markers of nutrition status, should not be considered in all patients as such since they are negative markers of inflammation and can be low in cases of GI or non‐GI losses . In specific instances, targeted micronutrient laboratory measurements of iron, vitamin D (and potentially other fat‐soluble vitamins), and zinc may be helpful.…”
Section: Nutrition Assessmentmentioning
confidence: 99%